Infection Control Protocol in Prosthetic Laboratory - Begum, Aleya; Ahmed, Rubaba; Dithi, Akashlynn Badruddoza; Islam, Md Saiful; Shaikh, Mushfiq Hassan (City Dental College Journal, 2013)
It is a public demand to expect health care profession to maintain its highest possible standard by preventing the spread of communicable diseases. Dental laboratory, being a potential source for the spread of various infections, is no exception to it and should ensure strict infection control measures. In contrast to the dental clinic and surgical areas, the dental laboratory is often overlooked, especially, when planning effective infection control measure. The aim of this review is to provide the general dental practitioners with the latest information and guidelines to achieve infection control in the dental laboratory. Apparently, it focuses on the technical knowledge and practices that should be followed in prosthetic laboratories. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16347 City Dent. Coll. J Voume-10, Number-2, July-2013